Strategi Penegakan Hukum terhadap Pelanggaran Prinsip Syariah dalam Transaksi Perbankan dan Keuangan Islam di Indonesia: Analisis Multi-Level Regulasi dan Mekanisme Pengawasan - Hajati, Nisa; Fikri, Ahmad Lutfi Rijalul; Supriyadi (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
This study analyzes multi-level law enforcement strategies against Sharia principle violations in Indonesian Islamic banking and finance, examining regulatory frameworks from national legislation (UU No. 21/2008) to institutional oversight by OJK, DSN-MUI, and Sharia Supervisory Boards. The research focuses on three primary violation categories: riba (interest-based transactions), gharar (excessive uncertainty), and maysir (speculative transactions), evaluating enforcement mechanisms across four levels: national regulatory framework, Sharia court adjudication (BASYARNAS and Religious Courts), institutional supervision (OJK and Bank Indonesia), and internal compliance systems. Using triangulation methods combining qualitative descriptive approaches with quantitative secondary data and legal document analysis (POJK regulations, DSN-MUI fatwas, court decisions), data was collected from academic sources, indexed journals, official legal documents, and international case studies. Key findings reveal enforcement fragmentation across regulatory levels, with gaps between UU 21/2008 provisions, POJK implementation, and DSN-MUI fatwa compliance. Religious Court decisions show inconsistent Sharia principle application, while OJK supervision data indicates varying compliance rates across violation categories. Current mechanisms suffer from regulatory fragmentation and lack of standardized protocols. The study develops an integrated multi-level Sharia law enforcement framework, comparing best practices from Malaysia, UAE, and other countries, recommending: (1) harmonizing multi-level regulatory frameworks; (2) strengthening OJK-DSN-MUI-Sharia court coordination; (3) standardizing violation categorization and sanctions; and (4) leveraging technology for compliance monitoring to create a more effective Sharia legal system